2008
DOI: 10.1001/archsurg.143.10.966
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatogastrostomy as a Salvage Procedure to Treat Severe Postoperative Pancreatic Fistula After Pancreatoduodenectomy

Abstract: Postoperative pancreatic fistula (POPF) is one of the most severe surgical complications of pancreatoduodenectomy (PD) with pancreaticojejunostomy (PJ) reconstruction. Recently, POPF has been classified as grade A, B, or C. Relaparotomy is mandatory for POPF associated with sepsis or hemorrhage (grade C). Peripancreatic drainage and completion pancreatectomy are the procedures most commonly used, but associated morbidity and mortality remain high. We hypothesized that the results of pancreatogastrostomy (PG) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 27 publications
1
33
0
2
Order By: Relevance
“…Two of them required additional operative pancreatic debridement and drainage procedures. These patients had long and complicated hospital courses, and 1 died after progressing to multiorgan failure.’ Bachellier et al [9] reported that they performed revision pancreaticogastrostomy during the secondary operation for patients with severe pancreatic fistula to substitute the original pancreaticogastrostomy (4 cases), and the results were satisfactory; however, 4 of 8 patients who underwent pancreatectomy died after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Two of them required additional operative pancreatic debridement and drainage procedures. These patients had long and complicated hospital courses, and 1 died after progressing to multiorgan failure.’ Bachellier et al [9] reported that they performed revision pancreaticogastrostomy during the secondary operation for patients with severe pancreatic fistula to substitute the original pancreaticogastrostomy (4 cases), and the results were satisfactory; however, 4 of 8 patients who underwent pancreatectomy died after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, surgery is imperative for patients with marked clinical worsening, inefficient percutaneous drainage of abscesses, vascular complications, progressive sepsis, oncoming organ failure, etc. These situations are commonly associated with elevated postoperative mortality (29).…”
Section: Pancreatic Fistula (Pf)mentioning
confidence: 99%
“…Mortality was 0 % after salvage pancreaticogastrostomy and 50 % after completion pancreatectomy. Despite retrospective and affected by selection bias, this data indicated that salvage pancreaticogastrostomy is a safe and efficient alternative to completion pancreatectomy for the treatment of grade C POPF after PD with pancreaticojejunostomy [50].…”
Section: Surgical Treatmentmentioning
confidence: 87%